Mechanisms and uncertainties of Zn supply on regulating rice Cd uptake - Cai, Yimin; Xu, Weibiao; Wang, Meie; Chen, Weiping; Li, Xuzhi; Li, Yonghui; Cai, Yaohui (Environmental pollution (1987), 2019)
Application of Zinc (Zn) is considered an effective measure to reduce Cadmium (Cd) uptake and toxicity in Cd-contaminated soils for many plant species. However, interaction between Zn and Cd in rice plant is complex and uncertain. In this study, four indica rice cultivars were selected to evaluate the effect of Zn exposure in an EGTA-buffered nutrient solution under varying Zn activities and a field level of Cd activity to characterize the interaction between Zn and Cd in rice. Severe depression in shoots’ biomass, tiller number, and SPAD (Soil and Plant Analyzer Development) value were found at both Zn deficiency and Zn phytotoxicity levels among four tested rice cultivars. There existed a strong antagonism interaction between Zn and Cd in both shoot and root from Zn deficiency to Zn phytotoxicity. The reduction of Cd accumulation in roots and shoots could be explained by the competition between Zn and Cd as well as the dilution effect of increasing biomass. The conflicting effect of Zn supply on Cd uptake may be attributed to the increasing transfer ratio of Cd from root to shoot with the increasing Zn2+ activities and the strong depression of Fe and Mn in shoots with the increasing Zn2+ activities as well as the variation of genotypes. Balance between Zn and Cd should be considered in field application. [Display omitted] •Antagonism between Zn and Cd in rice was observed from Zn deficiency to toxicity.•Cd transfer ratio from root to shoot increased with the increasing Zn2+ activities.•Conflict effects of Zn on Cd uptake and translocation resulted in uncertain effect. Main finding: Opposite results of Cd uptake and translocation could explain for the unstable effects of Zn on reducing rice Cd accumulation in practical application.